Determinants of Comparative Advantage in Services - Erik van der Marel (FIW - Research Centre International Economics, 2012)
This paper analyzes whether and to what extent determinants of comparative advantage have explanatory power for conventional services trade. It assesses the geographical, Heckscher-Ohlin and institutional determinants of services trade based on the literature for goods trade. Moreover, this paper investigates the importance of a country's governance of regulation as a source of comparative advantage in services markets. Determinants for services trade differ from goods. Services trade is more sensitive to a country's stock of high-skilled and mid-skilled labour, more receptive to the level of trust enjoyed by any importers, and more dependant on the quality of regulatory governance practiced when liberalizing services sectors. The counterfactual analyses presented in this paper show furthermore that these factors when affected by policy can bring substantial gains to countries. Specifically, countries with already good regulatory governance structures would enjoy relatively higher growth share in services trade by capitalizing on their highskilled stock. Other countries, however, would instead to better by improving their condition of regulatory governance.
Keywords: F13; L8; F15; 330; Trade in services; Comparative advantage; Institutions; Regulation integration